Analisa Penurunan Kadar COD Dan BOD Limbah Cair Laboratorium Biokimia UIN Makassar Menggunakan Fly Ash (Abu Terbang) Batubara - Rahmawati Rahmawati; St Chadijah; Asriani Ilyas (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
Fly ash coal has been used as adsorbents in reduction of pollutant parameters in the wastewater. Fly ash coal is a coal combustion residue in the form of fine particles and an inorganic material that is being developed potential for mineral adsorbent, so as to reduce environmental pollution. Activation of fly ash coal carried by soaking in solution H2SO4 1 M, then heated at a temperature of 450oC. The method used is a separate component that is specific adsorption of the fluid to the surface of solids. This study aims to determine how the effectiveness of fly ash coal as adsorbent in the lower levels of COD and BOD effluent Biochemistry laboratory at the State Islamic University of Alauddin Makassar. The results showed that the fly ash coal can be used to reduce the content of COD and BOD. COD and BOD levels before it is contacted with fly ash coal in a row 92 414 mg/L and 24 255 mg/L. After contacted with fly ash coal in optimum condition weighs 1.5 g and 90 rpm COD decreased to 33 005 mg/L and 32 062 mg/L, whereas at 2 g and 90 rpm BOD decreased to 17 325 mg/L and 10,395 mg/L.